Utricularia damingshanensis (Lentibulariaceae), a new species from Guangxi, China - Li, Zhi-Zhong; Wu, Shuang; Nong, Dong-Xin; Zhou, Guang-Rong; Zhou, Pi-Lin; Lin, Li; Ouyang, Xuhong; Jobson, Richard W.; Shao, Jian-Wen (Phytotaxa, 2025)
Utricularia damingshanensis (Lentibulariaceae), a new species from Guangxi, China, is described and illustrated. It resembles U. caerulea and U. warburgii but differs in having a corolla palate with four hooked processes on the distal margin; lower calyx lobe distinctly shorter than the upper; distinctly striped corolla with 8–15 deep violet lines on the lower lip and 6–9 radiating lines on the upper lip, as well as a helmet-like swelling at the base of the lower lip. Phylogenetic analysis based on nrITS, rps16, and trnD–trnT strongly supported its placement in sect. Nigrescentes as sister to U. warburgii. Both morphological and molecular evidence support its status as a new species.